Serie especial: La transición desde la delincuencia juvenil a la delincuencia adulta IV - Hoge, Robert D. (Revista Española de Investigación Criminológica, 2015)
This work is the fourth paper in the special series on Transition from juvenile to adult crime. The first paper (on criminal transition) was published in the number 9 of the REIC (2011), and the next two (respectively, on patterns of criminal career and theoretical explanations of criminal transitions) in the number 11 (2013). The specific purpose of this paper is to review the available scientific knowledge about early prediction of adult crime (aged 18-29 years). This review is based on research on youth development and risk prediction instruments. The paper opens with a general discussion of assessment and prediction, including risk prediction and its ethical and legal aspects. The main risk factors and technical issues that are associated with criminal activity are summarized. While the main risk assessment tools used with youth and adult offenders are reviewed. The work concludes with several recommendations, both for clinical applications and for research, regarding offender evaluation and risk prediction.